Halal Tourism: A Critical Review of the Development and Implementation - Adinda, Zachlul; Kusumasari, Bevaola; Hadna, Agus Heruanto; Susanto, Nurhadi (JKAP (Jurnal Kebijakan dan Administrasi Publik), 2024)
This research aims to comprehend the development of halal tourism by systematically reviewing articles on halal tourism using the Systematic Literature Review (SLR) method and qualitative approach. This study explores the topic of halal tourism with the objective of complementing various previous research endeavors. This study reviewed 119 articles using the keywords “halal tourism” and “Muslim-friendly tourism” within the Scopus database. This study revealed four main research streams in halal tourism literature: the definition, concept, opportunities, and implementation of halal tourism. The theoretical contributions of this study include clarifying the concept and definition of halal tourism, classifying research streams in halal tourism, and offering directions for future research through various research questions. The limitations of this study are primarily attributed to the use of the Scopus database as the primary and sole source of data and the limited scope of keywords employed.